Isolation of New Aliphatic Ester 8’a-Hydroxy-n-decanyl n-docosanoate from the Leaves of Centaurothamnus maximus Wagentz and Dittri - A. Siddiqui, Nasir; A. Al Anezi, Mohammed; Alam, Perwez; Haque, Anzarul; A. Basodan, Omer; J. Al Rehaily, Adnan; Ali, Mohammed (Asian Journal of Chemistry, 2015)
Centaurothamnus maximus (Asteraceae) is a wild and one of the least explored plants of Saudi Arabia. Yellow amorphous powder compound 1 (CM-1) was obtained after eluting the ethanol extract from reverse phase column (RP-18) by chloroform eluent of mobile phase. This is a new ester of decanediol esterified with behenic acid isolated for the first time from the plant source. The chemical structure of compound (CM-1) was established as 8'a-hydroxy-n-decanyl n-docosanoate after UV, IR, 1H NMR, 13C NMR, COSY, HSQC, HMBC and MASS spectroscopic studies. Two known compounds n-hexatriacosanoic acid (CM-2) and stigmasterol (CM-3) were also isolated and identified by spectroscopic studies.